The Needs Analysis for the Development of an Ethnoecological-STEAM Project-Based Learning Model with the Utilization of Water Hyacinth to Improve 21st Century 4C Skills for Students as Science Teacher Candidates - M. Hidayatur Rohman; Putut Marwoto; Sunyoto Eko Nugroho; Supriyadi Supriyadi (Universitas Negeri Semarang, 2023)
Students need to master 21st-century skills from primary education to higher education, the aim is to respond to the paradigms and characteristics of 21st-century education. One of the activities to answer the challenges of 21st-century education is the development of learning models. This study aims to analyze the need to develop learning models to improve 21st-century skills for prospective science teacher students. The research method used is an Exploratory Sequential Mixed Methods Design with three stages, while the general procedure for developing learning models uses the ADDIE method (Analyze, Design, Develop, Implement, and Evaluate). The needs analysis in this research is part of the qualitative exploration stage related to the first stage of data collection, and the second stage is about the draft model development, or in the ADDIE method, it is included in the analysis and design stage. The research subjects were 10 science lecturers, 33 science education students, and 37 science teachers at junior high schools in the Semarang district. The innovative model developed is an Ethnoecological-STEAM project-based learning model (PjBL E-STEAM) with the utilization of water hyacinth to improve 21st-century 4C skills for students as science teachers’ candidates. The results of the needs analysis are the initial product of the model development that will be piloted, namely the syntax of the PjBL E-STEAM model (Learn, Discuss, Perform, Elaborate, Convey, Practice, Evaluate, and Use), the PjBL E-STEAM based Learning Module, and instruments to measure 21st-century 4C skills.